A Comparative Study of the Weight and Height of Handball and Basketball Players - Ankitpuri D. Goswami (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The purpose of this research study was to conduct a comparative study of the weight and height of handball and basketball players. In this research study, a total of 40 players, 20 handball and 20 basketball players, aged 18 to 25 years, were selected as subjects. In the measurement standard, weight was measured using a weighing scale and height was measured using a steel tape. In this study, the significance was tested at the 0.05 level by applying the‘t’ ratio to compare weight and body height. The conclusion was as follows. No significant difference was found in the weight and height of handball and volleyball players.